Enhancing reflection on medical and surgical nursing among nursing students: A participatory action research study. (July 2021) - Lin, Chun-Chih; Han, Chin-Yen; Wu, Min-Lin (Winnie); Hsiao, Ping-Ru; Wang, Li-Hsiang; Chen, Li-Chin
Abstract: Background: Medical and Surgical Nursing (MSN) is a core course in baccalaureate nursing programs that requires active and effective teaching and learning strategies to enhance students' engagement. Objective: To develop and implement an effective learning process for students undertaking the MSN course. Design: This participatory action research study used reflection as the center of action in the cycle of planning, acting, observing and reflecting and re-planning. Setting: The study was conducted at a University in southern Taiwan. Participants: Thirty nursing students in their second year of a bachelor program in nursing, aged 19 to 20 years, were recruited via email and completed the study. Methods: The data were collected from February to June 2019 through reflective workshops, group discussions, individual interviews, and field notes. A qualitative content analysis was performed. Four criteria were considered to ensure the trustworthiness of the study process: reliability, validity, transferability, and authentic citations. Results: Four key themes – two challenges and two adaptive strategies - emerged in relation to the spiral process of improving teaching and learning in the MSN course. Participants experienced two main challenges: the large amount of multidisciplinary knowledge expected, and the rapid pace of the course. The two adaptive strategies were: recognizing their own unique way of learning and becoming an active learner and achiever. Conclusions: The project helped students to identify their own learning challenges, recognize the need to modify their attitudes and approaches to learning, improve teaching and learning in the MSN course, and identify the characteristics relevant to becoming an active learner and achiever.